Palliative care nursing for Buddhist Monk illness following dharma discipline (Tripitaka) - Artsanthia, Jintana; Kruasukon, Chawalee (Journal of The Royal Thai Army Nurses, 2020)
Palliative care is a special care for each patient that it is not specific formula in each nursing care. The nurses who care patients need to use the skill both in art and science by using integrations of western medicine and alternative medicine. Moreover, the nurses should consider in faith, hope, believe, life history and context of patient and family for appropriate of each patient that depend on the right or living will to choose when the end of life is coming. Palliative care nursing for Buddhist Monk illness following dharma discipline (Tripitaka) is an importance. If the monks have illness in the incurable disease and the perception of monks depend on the period of time to be the monk life, when they get sick and they need palliative care with the condition of no relative support, so it is an important role of nurses in caring following the right in welfare of monk patient. Hence, palliative care with the monk context following the dharma discipline (Tripitaka) has the meaning and it has an important to increase quality of life of the illness of the monks especially in psychological aspect in dharma practice following the wish of monk. That leads to set the nursing activities of good palliative care for the monks.